The Role Of Quality Management In Enhancing The Efficiency And Effectiveness Of Settling Accounts Tax(Empirical Study You Jordan Income &Sales Tax Department - محمد, صفاء احمد (Journal of Economics and Administrative Sciences, 2012)
This research aims to investigate the role of quality management in enhancing the efficiency and effectiveness of settling accounts tax in terms of achieving satisfaction in charge of the hand and the increase of tax revenue on the other hand, by testing the main hypothesis of the study and the sub-hypotheses in the Income and Sales Tax Department in Jordan for the period 2000-2010. The choice for this department is related to being the first Department in the Middle East and Arab world to get the ISO 9001.The results of the study confirms the presence of satisfaction in charge of the services provided by the department, which is reflected on the efficiency in the process of settling accounts of tax. Additionally, the results indicates an increase in tax revenue growth for the five years following the introduction quality management in the Jordanian Income and Sales Tax Department, which confirms that the efficiency in the process of settling accounts tax has been achieved.